A survey of herbal weeds that are used to treat gastrointestinal disorders from southern Thailand: Krabi and Songkhla provinces. (14th September 2017) - Neamsuvan, Oratai; Ruangrit, Thamakorn
Abstract: Ethnopharmacological relevance: Weeds are plants grow naturally and are commonly seen. They are mostly used for feedstuff. However, their use as herbs for treating diseases, including gastrointestinal disorders, is rare. Therefore, the present study aimed to: (1) quantify the number of herbal weeds used for treating gastrointestinal disorders; (2) study local knowledge of weed utilization for treating gastrointestinal disorders in Songkhla and Krabi provinces; and (3) analyse quantitative data with the Informant Consensus Factor (ICF), Use Value (UV) and Fidelity Level (FL). Materials and methods: The study was conducted from November 2014 to January 2016 through semi-structured interviews with 35 folk healers. The main questions were designed to obtain plant information, including the local name, method of use, preparation method and medicinal properties. The data were analysed by descriptive statistics, quantitative indexes (UV, ICF as well as FL) and interpretation. Results: A total of 49 species in 46 genera and 28 families were found. The most common use of weeds was as herbs (80%). The preferred part used was the whole plant (76.27%). The preferred methods of drug preparation and use were decoction and drink, respectively. The highest UV was found for Acmella oleracea (0.83). The highest FLs (100%) were found for 12 species, including Amaranthus spinosus, Amaranthus viridis, Alternanthera sessilis, Sauropus androgynus, Plantago major, and others. The highest ICF (0.93) was found for treating toothache. Conclusion: Overall, there are reports on the pharmacological activity of 31 species of weeds and reports on toxicity for 20 species of weeds. Therefore, awareness of the use of herbs is necessary to ensure that they are used safely and that benefits arise from the therapy. This study showed that medicinal weeds are still popularly used by folk healers. The pharmacological properties were consistent with the local uses, which supported a preliminary indication that the weed plants were effective for treating gastrointestinal diseases.